On Independence and Minimal Generating Set in Semigroups and Countable Systems of Semigroups. - Sampson, Marshal Imeh; ZSOLT, LIPCSEY; ACHUOBI, Jonas Ogar; IGIRI, CHRISTIANA; ESSIEN, LOUIS Effiong (International Journal of Mathematical Analysis and Modelling, 2023)
This paper studies independence in semigroup by exploring the relationship between the concepts of “minimal generating set” as compared to “minimum generating set” using comparability of elements, as induced by the orderings on the semigroup. It is shown that minimal generating set implies independence and vice versa. Two concluding results which are algorithms respectively for determining minimal generating sets for countable systems of semigroups and for any given semigroup, are given.